PERBANDINGAN PUTUSAN PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PENCURIAN DALAM KELUARGA - Dion Reyvaldo Sar Lopo (Jurnal Panah Hukum, 2023)
Theft is a crime that often occurs in society and can be committed by anyone, including our own family, theft committed by the family of the victim is called theft in the family. One of the crimes of theft in the family that has been examined and tried by the court is decision number 522/Pid.B/2020/PN Rhl and decision number 94/Pid.B/2021/PN Tar. In both decisions, the perpetrators were charged with Article 367 paragraph (2) of the Criminal Code. The type of research used is normative legal research with a statutory approach, case approach, comparative approach and analytical comparison. Data collection was carried out using secondary data obtained through library materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data analysis used is descriptive qualitative analysis and the conclusion is drawn using the deductive method. Based on the research findings and discussion, it can be concluded that the comparison of sentencing decisions against perpetrators of criminal acts of theft in the family (Decision Study Number 522/Pid.B/2020/PN Rhl and Decision Study Number 94/Pid.B/2021/PN Tar) is the difference in the sentences given, where the perpetrator Riki Fadli Alias ​​Riki Bin Umar in decision number 522/Pid.B/2020/PN Rhl was sentenced to a heavier sentence. That is for 1 (one) year in prison, while the perpetrator Muchlis Bin H. Agus Salim in the decision number 94/Pid.B/2021/PN Tar was sentenced to a lighter sentence with a long sentence of 6 (six) months in prison. The author suggests that the Panel of Judges in examining a case at trial must be more selective, proportional and wise as has been mandated by the applicable law, so that in deciding cases in decision number 522/Pid.B/2020/PN Rhl and decision number 94 /Pid.B/2021/PN Tar, the perpetrator can be sentenced according to the actions committed by the perpetrator and in accordance with the facts of the trial and the judge must also use conscience which is prioritized in deciding a case